GAME-BASED LEARNING MEDIA AND ITS EFFECT TOWARD STUDENTS’ LEARNING ACHIEVEMENT - Alifah Istiqamah Irhad; Wahyuni Ismail; Syahriani Syahriani; Syamsul Syamsul (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
This study aims to determine the effect of game-based learning media toward students’ learning achievement. The game-based learning media implemented during this study was Quizziz. This research design used a Non-equivalent control group design with Quasi Experiment method. The research sample comprised 20 students, ten from class XI MIPA 5 as an experimental class and ten from class XI MIPA 6 as a control class. The research instrument is a learning achievement test in the form of a pretest and posttest with as many as 15 questions numbers. Based on the game-based learning media analysis result, it shows that implementing learning using Quizizz game-based learning media is better than conventional learning methods. It can be seen from the calculation of the quizizz game media t-test shows that the sig t count is 0.000 0.05, then H1 is accepted, and H0 is rejected. The results of the score analysis averaged the completeness of the experimental class reached 76.40 with high criteria, while the conventional learning method in the control class of 65.90 with medium criteria. All in all, game-based learning media is proved that it affects in the students’ learning achievement on digestive system topic.